Combined in vitro and cell-based selection display method producing specific binders against IL-9 receptor in high yields - Huličiak, Maroš; Biedermanová, Lada; Berdár, Daniel; Herynek, Štěpán; Kolářová, Lucie; Tomala, Jakub; Mikulecký, Pavel; Schneider, Bohdan (The FEBS journal, 2023)
We combined cell-free ribosome display and cell-based yeast display selection to build specific protein binders to the extracellular domain of the human interleukin 9 receptor alpha (IL-9Rα). The target, IL-9Rα, is the receptor involved in the signalling pathway of IL-9, a pro-inflammatory cytokine medically important for its involvement in respiratory diseases. The successive use of modified protocols of ribosome and yeast displays allowed us to combine their strengths-the virtually infinite selection power of ribosome display and the production of (mostly) properly folded and soluble proteins in yeast display. The described experimental protocol is optimized to produce binders highly specific to the target, including selectivity to common proteins such as BSA, and proteins potentially competing for the binder such as receptors of other cytokines. The binders were trained from DNA libraries of two protein scaffolds called 57aBi and 57bBi developed in our laboratory. We show that the described unconventional combination of ribosome and yeast displays is effective in developing selective small protein binders to the medically relevant molecular target.
Keywords: Saccharomyces cerevisiae; vazba proteinů; peptidová knihovna; cytokiny; transportní proteiny; Peptide Library; Receptors, Interleukin-9; Carrier Proteins; lidé; Cytokines; receptory interleukinu-9; Protein Binding; Humans